Stabilisasi Tanah Lempung dengan Mengunakan Larutan Asam Sulfat (H2so4) pada Tanah Dasar di Daerah Godong - Purwodadi Km 50 Kabupaten Grogogan - Prabandiyani RW, Sri; Hardiyati, Siti; Muhrozi, Muhrozi; Pardoyo, Bambang (MEDIA KOMUNIKASI TEKNIK SIPIL, 2015)
An expansive clay soil material that is composed of various minerals include kaolinite, montmorillonite and illite group. Mineral montmorilinite have the sensitivity to the effects of the water is very easy to expand and contract. High and low levels of development (swelling) and shrinkage (shrinkage) expansive clay is determined by the high and low content of montmorillonite on expansive clay granules. Because of these properties are very high content of montmorillonite often cause problems in the building. This study uses a solution of sulfuric acid (H2SO4) as a stabilizer through the compaction process Modified Proctor on OMC Proctor standard by the number of collisions each is 10 x, 25 x and 56 x, and the amount of additional water in cc on dry ground, with variations in increments of 100%, water by 90%:10% H2SO4, water by 80%: 20% H2SO4 and water by 90%: 30% H2SO4. This research was conducted testing-testing in the laboratory include: physical properties, mechanical properties. swelling pressure, swelling potential and CBR with curing and no curing. Results of the test-the test, can increase the value of physical and mechanical properties, while pergujian against swelling pressure and swelling potential is not significantly increased.